Pengertian dan Konsep Pidana Koorporasi - Ragil Surya, Prakasa; Wulandari, Vadila; Suswanti, Nadya; Adiansyah, Dwi; Ramadhan, Fajar (ASOSIASI IDEBAHASA KEPRI, 2024)
Traditionally, criminal law only recognizes humans as subjects of criminal law or perpetrators of criminal acts. However, considering that many companies carry out various business activities that harm society in ways that violate the law, society and criminal law experts have begun to question: should companies whose business activities are very detrimental to society not have to bear the burden of criminal responsibility? Are only their managers able and must be punished? This question has led to the acceptance of the concept of corporate criminal responsibility. Criminal acts for which criminal responsibility can be imposed on corporations are called corporate crimes. The concept of corporate criminalization is a concept of criminal law that has not been accepted by criminal law for long. Although this concept first appeared in England in the 19th century, in other countries this concept was only accepted in the 20th century. For example, France only recognized the concept of corporations as perpetrators of criminal acts in 1994, Luxembourg and Spain in 2010, and Italy in 2011. The increasing number of criminal cases against corporations in the US and Canada also only occurred in the 21st century. The US and Europe in recent times have been faced with various criminal cases involving corporations, such as environmental pollution, unfair business competition, food and drug products that are harmful to health, fraud involving company accounting records, worker accidents, bribery, and financial crimes. The role of corporations is very large in human life on this earth. With human dependence on corporations that is very large, it is possible for corporations to do whatever they want, the most important thing for them is to get big profits. So it is not surprising if corporations violate the applicable regulations. In relation to this, can corporations be held accountable for these violations under Indonesian criminal law.